(untitled) (Italian Journal of Public Health, 2010)
Background: Violence against women is a recognized violation of human rights and an important public health concern. Violence during pregnancy is a risk to both the woman and her baby. Aims: The aim of this review was to identify what the literature reveals about violence during pregnancy in Asian countries. Methods: A systematic, integrated review was conducted of peer-reviewed literature published 1995-2009. Four databases were searched using the terms ‘intimate partner violence’, ‘domestic violence’, ‘pregnancy’, ‘Asia’, and ‘developing countries’. Reported results were compared within identified themes: prevalence, associated factors, interaction of violence and pregnancy, impact on women’s health, and the cultural role of children. Results: Twenty three eligible papers were found; 14 reported quantitative methods, 3 reported qualitative methods, and 6 reported both. Research was conducted in Bangladesh, Pakistan, India, China, Thailand, and Iran. The prevalence of violence during pregnancy ranged from 4.3% to 48%. Adverse effects of violence were evident on women’s physical and mental health and on their babies. Variables found to interact with violence were unintended pregnancy, woman’s age, partner’s education, social support, previous history of family violence, and the cultural value of children. The existing pattern and intensity of violence in the relationship were not found to change consistently with the woman’s pregnancy. Conclusions: The limited literature suggests that violence during pregnancy is a problem in at least some Asian countries as throughout the world. Further research is needed to increase knowledge of this important matter of significance both to women’s health and well-being and to social coherence.